ANALISIS KINERJA KEUANGAN ALOKASI DANA DESA - Manan, La Ode ABdul; Djauhar, Asri; Nurlela, Nurlela (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2022)
Financial Performance Analysis of Village Fund Allocation (Study in Lahunggumbi Village, Pondidaha District, Konawe Regency). This study aims to determine how well the financial performance of village fund allocations is based on the effectiveness ratio and growth ratio in Lahunggumbi Village, Pondidaha District, Konawe Regency. The type of research used in this research is quantitative. The data processed is the Village Fund Allocation Financial Report in the Village Revenue and Expenditure Budget from 2018 to 2020. The data collection techniques used are documentation techniques and library techniques. The data analysis technique used in this research is quantitative with the formula: Effectiveness Ratio and Growth Ratio. The results showed that in general the financial performance of the Lahunggumbi Village Government, Pondidaha District, Konawe Regency was good in managing the Village Fund Allocation finance. This can be seen from the calculation results of the Effectiveness Ratio categorized as Effective or Good, because the average effectiveness is 100%. While the Growth Ratio grew positively or well, because the average Village Fund Allocation Income Growth Ratio was 18,4% and the Village Fund Allocation Expenditure Growth Ratio was 18,4%.